Fertility Pattern Of Rural Women In Delhi - A Community Survey - Aggarwal O P; Rao Sarah S; Sethi Neeraj; Trikha V; Sharma S; Chutani C S (Wolters Kluwer Medknow Publications, 1986)
The present paper deals with the fertility of 676 unsterilized ever-married women of 15 years and above in two villages of Mehrauli block in Delhi during 1982-83. The average number of conceptions and live births were found to be 4.50 and 4.09 respectively. However, the average number of conceptions and live births to 60 years and above women, those who completed their period of fertility before the start of intensive family planning programme, were found to be 8.25 and 8.00 respectively. The average number of conceptions was almost half for women who had acquired any level of education as compared to illiterate women. Seven foetal deaths were reported per 100 conceptions by this study group.